PENGARUH LATIHAN STANDING BARBELL TRICEPS EXTENTION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU DALAM MELAKUKAN SERVIS ATAS PADA TEAM BOLA VOLI SMAN 2 PEKANBARU - Wahyudi, Novi; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research was conducted to determine whether there is influence of standing barbell triceps extention exercise on muscle strength of the arm and shoulder to men's volleyball team in SMAN 2 Pekanbaru, so that when serving on getting maximum results. This research is a form of research with experimental treatment to a population of men's volleyball player in SMAN 2 Pekanbaru. The data in this research is the entire population of 12 people. The instrument in this research is a expanding dynamometer test which aims to measure the strength of the arm and shoulder muscles. After that, the data is processed with statistical normality test with lillifors test at significant level 0,05????. The hypothesis is the influence of standing barbell triceps extention exercise on muscle strength of the arm and shoulder. Based on t test analysis produces Tcount is 8,14 and Ttable is 1,796, means Tcount > Ttable. Based on the analysis of statistical data, the average of Pre test is 18,00 and the average of past test is 21,83, so those data is normal. Thus, there is the influence of standing barbell triceps extention exercise on muscle strength of the arm and shoulder in serving on the men's volleyball team in SMAN 2 Pekanbaru.Keywords: standing barbell triceps extention, muscle strength of the arm and shoulder